Plant Peroxisomes: A Factory of Reactive Species - Corpas, Francisco J.; González-Gordo, Salvador; Palma, José M. (Frontiers in Plant Science, 2020)
Plant peroxisomes are organelles enclosed by a single membrane whose biochemical composition has the capacity to adapt depending on the plant tissue, developmental stage, as well as internal and external cellular stimuli. Apart from the peroxisomal metabolism of reactive oxygen species (ROS), discovered several decades ago, new molecules with signaling potential, including nitric oxide (NO) and hydrogen sulfide (H2S), have been detected in these organelles in recent years. These molecules generate a family of derived molecules, called reactive nitrogen species (RNS) and reactive sulfur species (RSS), whose peroxisomal metabolism is autoregulated through posttranslational modifications (PTMs) such as S-nitrosation, nitration and persulfidation. The peroxisomal metabolism of these reactive species, which can be weaponized against pathogens, is susceptible to modification in response to external stimuli. This review aims to provide up-to-date information on crosstalk between these reactive species families and peroxisomes, as well as on their cellular environment in light of the well-recognized signaling properties of H2O2, NO and H2S.